2008
DOI: 10.1071/sb07030
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of Gompholobium (Leguminosae: Mirbelieae)

Abstract: A taxonomic revision is presented of the Australasian legume genus Gompholobium Sm. The group includes 44 species, the following six of them newly described here: Gompholobium gairdnerianum Chappill, G. glutinosum Chappill, G. karijini Chappill, G. pungens Chappill, G. roseum Chappill and G. wonganense Chappill. Gompholobium asperulum (S.Moore) Crisp is recognised here as a nomenclatural synonym of G. shuttleworthii Meisn. The taxon that has been known under the former name is renamed as Gompholobium cinereum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…and Latrobea Meisn., and the inflated globose or ellipsoid fruit, a feature shared with Sphaerolobium Sm. In addition, Chappill et al (2008) indicated that seeds of all observed Gompholobium species have much longer (> 2 mm) funicles than those of other observed legume genera, a feature also noted by Cameron (1988) in a study of the embryology of Australian legume genera. Chappill et al (2008) also described a new species, G. karijini Chappill, to separate material from the Hamersley Range from the somewhat similar G. polyzygum F.Muell., which occurs to the east and south of the Pilbara bioregion.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…and Latrobea Meisn., and the inflated globose or ellipsoid fruit, a feature shared with Sphaerolobium Sm. In addition, Chappill et al (2008) indicated that seeds of all observed Gompholobium species have much longer (> 2 mm) funicles than those of other observed legume genera, a feature also noted by Cameron (1988) in a study of the embryology of Australian legume genera. Chappill et al (2008) also described a new species, G. karijini Chappill, to separate material from the Hamersley Range from the somewhat similar G. polyzygum F.Muell., which occurs to the east and south of the Pilbara bioregion.…”
Section: Introductionsupporting
confidence: 70%
“…In addition, Chappill et al (2008) indicated that seeds of all observed Gompholobium species have much longer (> 2 mm) funicles than those of other observed legume genera, a feature also noted by Cameron (1988) in a study of the embryology of Australian legume genera. Chappill et al (2008) also described a new species, G. karijini Chappill, to separate material from the Hamersley Range from the somewhat similar G. polyzygum F.Muell., which occurs to the east and south of the Pilbara bioregion. Chappill noted that the new species was variable; the type specimen is almost glabrous, while the remainder of the collections included by Chappill in G. karijini are villous.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…[44,71,[84][85][86], Gompholobium Sm. [87][88][89], Jacksonia [90], Leptosema Benth. [91], Phyllota [92], Pultenaea [93][94][95][96][97], and Stonesiella Crisp & P.H.…”
Section: Species-level Questionsmentioning
confidence: 99%